REAGIN-SPECIFIC RESPONSE TO INSULIN LEVEL IN CARBOHYDRATE METABOLISM DISORDERS IS DEPENDENT ON THE BLOOD GROUP ABO ANTIGENIC DETERMINANTS - N. R. Telesmanich (SPb RAACI, 2018)
The paper presents evidence that the individuals with different blood groups and glucose levels exhibit individual IgE reagin responses to insulin. Thus, the persons with 0 (I) blood group showed the highest values of anti-insulin-specific IgE (124.83±67.9 kE/L) when their glucose level was under 4 mmol/l. Such values are characteristic to the patients with A (II) and B (III) blood groups with normal glucose levels. Among subjects with B (III) blood group showing decreased glucose values (< 4 mmol/L), the lowest insulin induction (0.85±0.05 mkE/ml) was observed, and the IgE production to insulin increased 80-fold, reaching 113.0±56.0 kE/L. At the first ("borderline") stage of carbohydrate metabolism disorders (glucose levels 6.0 to 7.6 mmol/L), the insulin production is increased 3-fold in 0 (I) and A (II) blood groups, whereas insulin levels in persons with B(III) blood group are near-normal (12.3±3.7), and IgE antibodies to insulin show lowest levels (27.2±9.08 kE/L), thus being 5 times lower when compared to the persons with B (III) blood group. However, carriers of all three group antigens and patients with expressed type 2 diabetes respond to increased glucose and insulin levels in blood by decreased production of specific IgE antibodies to insulin.